The architecture and biology of soils : life in inner space - Ritz, K. (Karl); Young, Iain, 1962- (Wallingford, Oxfordshire ; Cambridge, MA : CABI, 2011)
Soil is a fundamental and critical, yet often overlooked, component of terrestrial ecosystems. It is an extremely complex environment, supporting levels of diversity far greater than any ecosystem above ground. This book explores how soil structure develops and the consequences this has for life underground. The effects of spatial arrangement, of soil's physical and biological components on their interaction and function are used to demonstrate their roles in ecosystem dynamics.
Views of the underworld: in situ visualization of soil biota -- Modelling soil structure and processes -- Microbial regulation of soil structural dynamics -- The zoological generation of soil structure -- Biotic regulation: plants -- Biota-mineral interactions -- How do the microhabitats framed by soil structure impact soil bacteria and the processes that they regulate? -- Fungal growth in soils -- Sensory ecology in soil space -- Managing the interactions between soil biota and their physical habitat in agroecosystems --Contaminated soils and bioremediation: creation and maintenance of inner space -- Biological interactions within soil profiles engineered for sport and amenity use.
Includes bibliographical references and index.
Keywords: Soil structure; Soil biology; Soil ecology